ERAP1/ERAP2 and RUNX3 polymorphisms are not associated with ankylosing spondylitis susceptibility in Chinese Han. (30th March 2018) - Su, W; Du, L; Liu, S; Deng, J; Cao, Q; Yuan, G; Kijlstra, A; Yang, P
Summary: Previous studies show that endoplasmic reticulum-associated aminopeptidase (ERAP1/ERAP2) and runt-related transcription factor 3 (RUNX3) gene polymorphisms are associated with AS (ankylosing spondylitis) in European Caucasians. However, contradictory results were reported in different Asian populations. The purpose of this study was to determine whether eleven candidate single nucleotide polymorphisms (SNPs) in ERAP1/ERAP2 and six in RUNX3 genes confer susceptibility to AS with or without acute anterior uveitis (AAU) [AS + AAU + or AS + AAU – ] in Chinese Han. Therefore, a case–control association study was performed in 882 AS + AAU −, 884 AS + AAU + and 1727 healthy controls. Genotyping was performed using the iPLEXGold genotyping assay. A meta-analysis was performed to assess the association of polymorphisms of ERAP1 with AS susceptibility in Asian populations. No association was found between SNPs of ERAP1/ERAP2/RUNX3 and susceptibility of AS with or without AAU. A case–control study between patients with human leucocyte antigen HLA-B27-positive and healthy controls also failed to demonstrate an association of the tested SNP with AS with or without AAU. Moreover, a meta-analysis showed that there was no association of rs30187, rs27037, rs27980, rs27434 and rs27582 in ERAP1 with AS in Chinese Han. Taken together, 17 SNPs in ERAP1/ERAP2 and RUNX3 genes did not confer disease susceptibility to AS in Chinese Han. Graphical Abstract: